Tick-Borne Encephalitis Virus Vaccination among Tourists in a High-Prevalence Area (Italy, 2023): A Cross-Sectional Study - Matteo Riccò; Silvia Corrado; Federico Marchesi; Marco Bottazzoli (Tropical Medicine and Infectious Disease, 2023)
Tick-borne encephalitis (TBE) represents a potential health threat for tourists in high-risk areas, including the Dolomite Mountains in northeastern Italy. The present questionnaire-based survey was, therefore, designed in order to assess knowledge, attitudes, and preventive practices (KAP) in a convenience sample of Italian tourists visiting the Dolomite Mountains, who were recruited through online discussion groups. A total of 942 participants (39.2% males, with 60.2% aged under 50) filled in the anonymous survey from 28 March 2023 to 20 June 2023. Overall, 24.1% of participants were vaccinated against TBE; 13.8% claimed to have previously had tick bites, but no cases of TBE were reported. The general understanding of TBE was relatively low; while 79.9% of participants acknowledged TBE as a potentially severe disease, its occurrence was acknowledged as high/rather high or very high in the Dolomites area by only 51.6% of respondents. Factors associated with the TBE vaccine were assessed by the calculation of adjusted odds ratios (aOR) and 95% confidence intervals through a logistic regression analysis model. Living in areas considered at high risk for TBE (aOR 3.010, 95%CI 2.062–4.394), better knowledge on tick-borne disorders (aOR 1.515, 95%CI 1.071–2.142), high risk perception regarding tick-borne infections (aOR 2.566, 95%CI 1.806–3.646), a favorable attitude toward vaccinations (aOR 3.824, 95%CI 1.774–8.224), and a tick bite(s) in a previous season (aOR 5.479, 95%CI 3.582–8.382) were characterized as being positively associated with TBE vaccination uptake. Conversely, being <50 years old (aOR 0.646, 95%CI, 0.458–0.913) and with a higher risk perception regarding the TBE vaccine (aOR 0.541, 95%CI 0.379–0.772) were identified as the main barriers to vaccination. In summary, tourists to the high-risk area of the Dolomites largely underestimate the potential occurrence of TBE. Even though the uptake of the TBE vaccine in this research was in line with European data, public health communication on TBE is required in order to improve acceptance of this effective preventive option.